The Effect of Teachers’ Perceptions on Principal’s Leadership and Teaching Motivation on Teacher Performance in Learning - Nurdin Nurdin (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine the magnitude of the influence of teacher perceptions of principals 'leadership and motivation to propel teachers' performance in learning. This research method is survey research. The subjects of this study were 80 teachers taken randomly at Tambun-Bekasi 2 High School. Data was collected by questionnaire instruments using skla likert. The validity of the data is obtained by validity and reliability, all data has a normal distribution. The results of the study showed that teachers 'perceptions of principals' leadership had a significant influence on teacher performance in learning. Likewise the motivation of teaching gives a significant influence on teacher performance in learning. The coefficient of determination (R)2 is the teacher's perception of the principal's leadership and teaching motivation has a less strong relationship to teacher performance in learning.